2019
DOI: 10.1002/jssc.201900302
|View full text |Cite
|
Sign up to set email alerts
|

Identification of flavonoids and chlorogenic acids in elm fruits from the genus Ulmus and their antioxidant activity

Abstract: Elm fruits were once an important food source in the years of famine. Research on the functional compounds in elm fruits was almost unavailable. In this study, we established an efficient high‐performance liquid chromatography method for the simultaneous separation of eight chlorogenic acids and 28 flavonoids in elm fruits for the first time. Total flavonoid contents ranged from 286 mg/100 g (Ulmus laciniata) to 1228 mg/100 g (U. pumila). High concentrations of rutin, quercetin 3‐O‐glucoside, and kaempferol de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…Major bioactive compounds identified in N. officinale are acetic acid, D-alanine, octodrine, and cyclohexylethylamine. The compounds of N. officinale were identified at their specific retention times, as previously identified by Mehtaet al, Erian et al, and Seal [19,20,25,42]. Such match similarity is reported to be an indication of well separation and spectral purity [45].…”
Section: Phytochemical Analysissupporting
confidence: 56%
See 1 more Smart Citation
“…Major bioactive compounds identified in N. officinale are acetic acid, D-alanine, octodrine, and cyclohexylethylamine. The compounds of N. officinale were identified at their specific retention times, as previously identified by Mehtaet al, Erian et al, and Seal [19,20,25,42]. Such match similarity is reported to be an indication of well separation and spectral purity [45].…”
Section: Phytochemical Analysissupporting
confidence: 56%
“…Different methods have been reported in the literature for determination of phytochemicals via HPLC, MS, UV, etc. [38][39][40][41][42][43]. Moreover the GC-MS provides scientific world a more economic and efficient option to scrutinize key fermentation products such as volatile fatty acids, acetic acid, esters, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A positive coefficient indicates that it is positively correlated with the enzyme activity, while a negative number indicates that it is negatively correlated with the enzyme activity. The IC 50 for XO activity increased with increasing peak areas of 3,4,7,10,11,16,17,18,20,21,23,24,25,26,27,28, and 30, indicating that this component group was positively correlated with XO inhibitory activity and that peaks 1,2,5,6,8,9,12,13,14,15,19,22,31,32, and 33 were negatively correlated with their inhibitory activities ( Figure 6). Variable importance in projection (VIP) scores is important indicators that reflect the ability of independent variables to explain dependent variables.…”
Section: Plsr Analysis Resultsmentioning
confidence: 98%
“…These methods enable rapid analysis, complement their respective advantages, and can be used to comprehensively evaluate the quality of L. lucidum. GRA showed that the main components responsible for the XO inhibitory activity of L. lucidum might be characteristic peaks 1,2,4,5,6,7,8,9,11,12,14,15,16,17,20,21,23,25,27,28,29,31,32, and 33. PLS analysis showed that peaks 1, 2, 4, 5, 6, 7, 14, 17, 22, 24, 25, 28, 31, F I G U R E 6 Effect coefficient of each chromatographic peak on the xanthine oxidase inhibitory activity F I G U R E 7 VIP contribution of each characteristic peak to the antioxidant activity of Ligustrum lucidum and 33 had significant effects on the XO inhibitory activity.…”
Section: Plsr Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation